The Power of Collateral : How Problems in Securing Transections Limit Private Credit from Movable Property - Fleisig, Heywood (World Bank, Washington, DC, 2012)
In many developing countries, faulty laws and regulations make it hard to use livestock, machines, equipment, standing crops, and other movable property as collateral. The resulting constraints on access to credit hurt economies. In Bolivia, for example, a faulty legal and regulatory framework for the use of movable property as collateral has led to a loss in GDP estimated at between 5 and 10 percent. The author explains the problem.